Phase IV head‐to‐head randomized controlled trial comparing ingenol mebutate 0·015% gel with diclofenac sodium 3% gel for the treatment of actinic keratosis on the face or scalp. (15th January 2018) - Stockfleth, E.; Harwood, C.A.; Serra‐Guillén, C.; Larsson, T.; Østerdal, M.L.; Skov, T.
Summary: Background: Ingenol mebutate (IngMeb) and diclofenac sodium (DS) are approved treatments for actinic keratosis (AK). Objectives: To compare the efficacy and safety of IngMeb 0·015% gel with DS 3% gel (NCT02406014). Methods: Patients with 4–8 visible, discrete AK lesions on the face/scalp in a 25 cm 2 contiguous area of skin were randomized 1:1 to IngMeb once‐daily for three consecutive days or DS twice‐daily for 90 days. Patients with AK lesions at Week 8 following IngMeb were offered a second IngMeb course. Primary end point was complete clearance of AK lesions (AKCLEAR 100) at end of first treatment course (Week 8, IngMeb; Week 17, DS). Secondary end points included AKCLEAR 100 at end of last treatment course and Week 17; adverse events (AEs) were assessed at these time points. Patients completed treatment satisfaction questionnaires for medication (TSQM; Week 17). Results: AKCLEAR 100 at end of first treatment course was higher with IngMeb (34%) vs. DS (23%; P = 0·006). AKCLEAR 100 at end of last IngMeb course (53%) and Week 17 (45%) was higher than DS (both P < 0·001). The most frequent AE was application‐site erythema (IngMeb 19%; DS 12%). Treatment‐related AE (TRAE) duration was shorter with IngMeb. TRAE withdrawals were lower for IngMeb (2%) vs. DS (6%). TSQM scores for global satisfaction ( P < 0·001) and effectiveness ( P = 0·002) were higher with IngMeb, as was dosing instruction adherence (≥ 90% vs. 70%). Conclusions: AKCLEAR 100, patient treatment satisfaction and effectiveness were significantly higher with IngMeb compared with DS, demonstrating superiority of IngMeb for AK treatment on face/scalp. Abstract : What's already known about this topic? Actinic keratosis (AK) manifests as clinical and subclinical lesions on a disease continuum with squamous cell carcinoma in areas of sun‐induced field cancerization. Field treatments for AK may be advantageous as they treat the whole cancerized field, including subclinical lesions, vs. lesion‐directed therapies, which only treat visible lesions. Ingenol mebutate (IngMeb) and diclofenac sodium (DS) are approved treatments for AK in areas of skin up to 25 cm 2 . What does this study add? This was the first head‐to‐head comparison of IngMeb and DS, evaluated in a randomized controlled trial with minimum visits to reflect real life. Three‐day IngMeb treatment demonstrated significantly greater efficacy compared with 90‐day DS treatment for AK on the face and scalp. Both treatments were well tolerated; the short treatment duration with IngMeb may have contributed to superior patient satisfaction with treatment over DS. Linked Comment: Bagatin. Br J Dermatol 2018;178 :322–323 . Plain language summary available online Respond to this article